Assessment Of Hydraulic Response Due To Flood Mitigation Measures In Sg. Pinang Catchment, Penang - Low, Chee Soon (1995)
The current study aims to assess the hydraulic response of Sg. Pinang catchment under both existing and proposed conditions, by means of the advanced flow simulation model SWMM developed by the USEPA.